Evaluation of serum hepcidin in assessment of iron status in renal transplant patients - El-Khatib, Mohamed; Fawzy, May; El-Khashab, Sahier; Ramzy, Maher Fouad; Elgayar, Dina; Kamal, Manal (African Journal of Nephrology, 2010)
<p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Background: Hepcidin is a 25 aminoacid peptide that isproduced primarily by the liver in response to a varietyof stimuli known to modulate tissue iron stores and itsserum availability. It circulates in plasma, is filtered bythe kidney, and accumulates in urine. The presence ofhepcidin in the plasma negatively regulates the egress ofiron from the cells and macrophages, involved intransport of iron into the extracellular spaces. Hepcidinbinds to ferroportin 1 present on the cell surface leadingto the internalization of ferroportin 1 and subsequentdegradation. Hepcidin has also been shown to be anacute phase reactant increased by interleukin 6 (IL-6) andmarkedly induced by infection and inflammation.Documentation of the role of hepcidin in thedevelopment of anemia in chronic kidney disease andwhether it can be used as a marker of iron status inchronic kidney disease (CKD) has been sought in manystudies.The aim of this study was to detect the value of hepcidinas a marker of iron status in post renal transplantrecipients as compared with chronic renal failure (CRF)patients on hemodialysis. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: In our study we found the level of serumprohepcidin in the renal transplant recipient group to becomparable to the control group. In the group with CKDthe serum prohepcidin was significantly lower thancontrols as well as the transplant recipients (p-value:0.00). There was no significant difference between theCKD group with higher hemoglobin and those withlower hemoglobin. From the correlation between theacute phase proteins and prohepcidin we found a positivecorrelation between serum ferritin, CRP and prohepcidinonly in the group with CKD on hemodialysis. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: We suggest that serum prohepcidin can be used as a routine measurement in transplant recipients as an indicator of the iron stores in the body. Further dedicated studies on large groups of patients need to be done to verify the usefulness of such a test.